Electrophysiological mapping of the epicardium via 3D‐printed flexible arrays - Terrence Pong; Kevin J. Cyr; Cody Carlton; Joy Aparicio‐Valenzuela; Hanjay Wang; Meghedi Babakhanian; Alessandro Maiuolo; Haley Lucian; Paul J. Wang; Y. Joseph Woo; Anson M. Lee (Wiley, 2023)
Abstract Cardiac electrophysiology mapping and ablation are widely used to treat heart rhythm disorders such as atrial fibrillation (AF) and ventricular tachycardia (VT). Here, we describe an approach for rapid production of three dimensional (3D)‐printed mapping devices derived from magnetic resonance imaging. The mapping devices are equipped with flexible electronic arrays that are shaped to match the epicardial contours of the atria and ventricle and allow for epicardial electrical mapping procedures. We validate that these flexible arrays provide high‐resolution mapping of epicardial signals in vivo using porcine models of AF and myocardial infarction. Specifically, global coverage of the epicardial surface allows for mapping and ablation of myocardial substrate and the capture of premature ventricular complexes with precise spatial-temporal resolution. We further show, as proof‐of‐concept, the localization of sites of VT by means of beat‐to‐beat whole‐chamber ventricular mapping of ex vivo Langendorff‐perfused human hearts.